2015
DOI: 10.1097/bpb.0000000000000211
|View full text |Cite
|
Sign up to set email alerts
|

Are patient demographics different for early-onset and late-onset Blount disease? Results based on meta-analysis

Abstract: Early-onset and late-onset Blount disease has been described with some clinical overlap between the two forms. Using PRISMA guidelines, we searched for articles that included demographics of patients with both types of Blount disease. On the basis of 24 articles that met our inclusion criteria, patients with early-onset Blount disease were more likely to have bilateral involvement [odds ratio (OR) 4.30, 95% confidence interval (CI) 2.27-8.17] and less likely to be Black (OR 0.20, 95% CI 0.08-0.53) or male (OR … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
36
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(40 citation statements)
references
References 39 publications
3
36
0
1
Order By: Relevance
“…1,2,9,10 A number of studies show a strong correlation between Blount's disease and obesity. 3,[10][11][12][13][14] Lisenda et al found no independent association between vitamin D deficiency and Blount's disease in their study in South African children. 15 Obesity has been shown to greatly increase the medial compartment pressure and contribute to the development of Blount's disease by the Heuter-Volkmann principle.…”
Section: Introductionmentioning
confidence: 64%
See 3 more Smart Citations
“…1,2,9,10 A number of studies show a strong correlation between Blount's disease and obesity. 3,[10][11][12][13][14] Lisenda et al found no independent association between vitamin D deficiency and Blount's disease in their study in South African children. 15 Obesity has been shown to greatly increase the medial compartment pressure and contribute to the development of Blount's disease by the Heuter-Volkmann principle.…”
Section: Introductionmentioning
confidence: 64%
“…1,2 Blount's disease is classified into early-onset (infantile) and late-onset based on whether the limb deformity develops before or after the age of four years. [2][3][4] It is classified radiologically by Langenskiold into six progressive stages per severity of the deformity to help in prognosticating patients' outcome. [4][5][6][7] The incidence of Blount's disease in South Africa was estimated to be 0.03% three decades ago.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…С учетом клинико-рентгенологических характеристик, с нашей точки зрения, выделение двух основных форм -инфантильной и подростковой -является наиболее целесообразным. Для инфантильной формы в большей степени характерны двустороннее поражение, более выраженная степень деформации, преобладание пациентов женского пола [14].…”
unclassified